The Correlation of Self-Confidence, Concentration, and Goal Setting with Routine Training Scores among Archery Athletes at BPPLOP Central Java - Richa Lintang Amtajawi; Heny Setyawati; Tommy Soenyoto (Journal of Physical Education and Sports, 2026)
In sports, there are several contributing factors including physical, technical, and psychological aspects. Among these, psychological factors particularly an athlete’s mental abilities play a significant role in performance. This study aims to examine the relationship between self-confidence, concentration, and goal setting on routine training scores. This research employed a test survey with a correlational approach and a cross-sectional design, meaning data was collected at one point in time. The sample consisted of 15 athletes, selected using a total sampling technique. The instruments used to collect data included: (1) Self-Confidence Scale, (2) Grid Concentration Test (GCT), (3) Goal Setting Scale, and (4) Training Score records. The results showed a strong and positive correlation between self-confidence, concentration, and goal setting with routine training scores. Specifically, self-confidence had a significant correlation with training scores (Sig. 2-tailed = 0.004), concentration (Sig. 2-tailed = 0.000), and goal setting (Sig. 2-tailed = 0.025). Furthermore, the combined influence of self-confidence, concentration, and goal setting on training scores was also significant, with a Sig. F Change value of 0.000 and an R square (R²) of 0.852. This indicates that 85.2% of the variance in training scores can be explained jointly by these three variables. The study concludes that self-confidence, concentration, and goal setting are significantly and simultaneously associated with routine training scores. The development of psychological aspects such as self-confidence, the ability to focus, and structured training goals is a crucial part of athlete development, particularly for archers in the BPPLOP Archery Program of Central Java, in order to achieve optimal training outcomes.